ANALISA KINERJA DAN TINGKAT PELAYANAN SIMPANG BERSINYAL KAPTEN A. RIVAI DENGAN METODE PKJI 2023 - Alzahri, Syahril; Zulkarnain, Yules Pramona; Misdalena, Felly; Fathurrahman, Muhammad (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
Palembang is one of the major cities in Indonesia that has undergone rapid growth, particularly in infrastructure and transportation. This development has led to a significant increase in vehicle numbers and heavy traffic flow, which is further worsened by side-friction activities that cause vehicle congestion, delays, and increase the risk of accidents. As a result, these traffic conditions reduce the comfort and safety of road users. The Kapten A. Rivai intersection, the focus of this study, serves as a key junction in Palembang, connecting office districts, shopping centers, and schools. The problem addressed in this research is how to analyze the performance and Level of Service (LOS) of the signalized intersection at Kapten A. Rivai using the PKJI 2023 method, with the goal of assessing the intersection’s overall performance and service quality. The findings show that during the evening peak hour on Tuesday (5:00 PM – 6:00 PM), the highest traffic volume at the Kapten A. Rivai intersection was recorded on the Jaksa Agung Soeprapto approach, with a capacity of 699 vehicles/hour and a saturation degree of 0.9. The average delay at the intersection was 49.57 seconds/vehicle, placing its Level of Service (LOS) in category E.